The value of sensory nerve conduction studies in the diagnosis of Guillain–Barré syndrome. Issue 5 (May 2021) - Freiha, Joumana; Zoghaib, Romy; Makhoul, Karim; Maalouf, Nancy; Riachi, Naji; Chalah, Moussa A.; Ayache, Samar S.; Ahdab, Rechdi
Highlights: Electrodiagnostic (EDX) criteria for GBS that rely on motor nerve conduction studies (NCS) are suboptimal early in the course of the disease and for GBS variants. Sensory NCS show added diagnostic value in GBS. EDX criteria should be reconsidered in the future in an attempt to optimize their diagnostic yield. Abstract: Electrophysiology plays a determinant role in Guillain–Barré syndrome (GBS) diagnosis, classification, and prognostication. However, traditional electrodiagnostic (EDX) criteria for GBS rely on motor nerve conduction studies (NCS) and are suboptimal early in the course of the disease or in the setting of GBS variants. Sensory nerve conduction studies, including the sural-sparing pattern and the sensory ratio are not yet included in EDX criteria despite their well-established role in GBS diagnosis. The aim of this review is to discuss the diagnostic value of sensory NCS in GBS, their role in establishing the diagnosis and predicting the outcome according to the various subtypes of the disease.